Religion and Sustainable Urban Planning: 'If you can't count it, or won't count it, it doesn't count'. (May 2016) - Greed, Clara
Abstract: Sustainability objectives are central to modern urban planning. Originally, sustainability had three components, environmental sustainability, economic well‐being and social equality: planet, prosperity and people. However, the environmental aspects of sustainability have tended to predominate. This leaves little space for social issues and aspatial (non‐physical) factors such as belief and religion. It is argued, with reference to UK‐related research, that religion has major spatial planning implications for all aspects and levels of urban policy. Neglecting religion's existence results in an incomplete planning agenda, undermining equality and diversity objectives. The implications of this gap are discussed with reference to the environmental, economic and social components of sustainability policy. There is little recognition of the contribution of religion to cities: rather, a negative mentality predominates amongst planners. Ways of changing the planners' understanding and mainstreaming religion into planning are discussed, drawing on methods used to integrate gender into planning. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment.